A MAGNESIUM-ENHANCED LIME CLEANING PROCESS OF FLUE GASES - Bricl, Martin; Avsec, Jurij (Journal of Energy Technology, 2024)
The cleaning of flue gases in thermal power plants has been mandatory since the 1990s in the EU. The most commonly applied process for flue gas cleaning is a wet calcite process that enables the high efficiency of cleaning flue gases with the usage of a reagent that is readily available in nature. This paper presents the process of cleaning the flue gases on a wet basis, but using slaked lime with the contentof the magnesium as the reagent. This sort of cleaning process works very well, but the reagent is usually very difficult to find in nature itself.